2020
DOI: 10.1080/15538362.2020.1862734
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Diversity of Walnut (Juglans regia L.) Among Two Major Areas in Morocco in Contrast with Foreign Varieties

Abstract: In Morocco, walnut tree (Juglans regia L.) cultivation is ancestral with complicated misidentification and unknown local genetic diversity. Atlas Mountains host a rich walnut tree germplasm, which has arisen from seedlings. The use of molecular markers makes it possible to overcomes confusion usually encountered in phenotypic characterization, thereby elucidating the real genetic diversity magnitude. This study aimed to investigate the genetic relationships among 33 local walnut trees grown in two contrasted a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…In this study by using 13 primers, 120 ISSR markers (reproducible) were generated, demonstrating the high rate of polymorphism among genotypes with 7 to 13 bands and an average of nine bands per primer. According to these investigations, the overall polymorphism level (average) was 75.2%, with an average polymorphic informativeness content of 0.32 and a range of 0.212 to 0.370 ( Houmanat et al., 2020 ). From these studies, it was concluded that ISSR markers were found to be more systematic in measuring the genetic diversity of walnut genotypes among two major areas in Morocco in comparison with foreign varieties as reported by Houmanat et al.…”
Section: Genetic Diversity Assessmentmentioning
confidence: 98%
“…In this study by using 13 primers, 120 ISSR markers (reproducible) were generated, demonstrating the high rate of polymorphism among genotypes with 7 to 13 bands and an average of nine bands per primer. According to these investigations, the overall polymorphism level (average) was 75.2%, with an average polymorphic informativeness content of 0.32 and a range of 0.212 to 0.370 ( Houmanat et al., 2020 ). From these studies, it was concluded that ISSR markers were found to be more systematic in measuring the genetic diversity of walnut genotypes among two major areas in Morocco in comparison with foreign varieties as reported by Houmanat et al.…”
Section: Genetic Diversity Assessmentmentioning
confidence: 98%
“…The phenological and morphological characters are rather affected by environmental conditions. So, during recent decades many studies have focused on morphological traits with molecular techniques, such as DNA-based markers SSR, ISSR, AFLP, RAPD, and SNP (Single-nucleotide polymorphism) to reveal genetic diversity, relationships among cultivars or genotypes, explain phylogenetically and origin in walnut (Fjellstrom et al, 1994;Nicese et al, 1998;Kafkas et al, 2005;Christopoulos et al, 2010;Orhan et al, 2020;Houmanata et al, 2021). The percentage polymorphism and the average polymorphic band per primer detected in our present results were higher than previously found by İpek et al (2018) and Doğan et al (2010).…”
Section: Correlations and Multivariate Analysis Among The Charactersmentioning
confidence: 99%
“…In medicinal flora, Morocco is one of the most important diversities of the Mediterranean basin, particularly for tree species including olive, fig, and walnut [ 11 ]. The most important areas of walnut were identified in the Rif, High, and Medium Atlas mountains and in arid regions in Southeastern Morocco [ 12 ].…”
Section: Introductionmentioning
confidence: 99%